The Mechanisms of Insect Cognition - Giurfa, Martin; Riffell, Jeffrey A.; Chittka, Lars (Frontiers Media SA, 2020)
The last 15 years have generated a wealth of information on cognitive function in insects. This includes work on attention-like processes, categorization of visual stimuli (for example symmetrical vs. asymmetrical ones), concept learning, context learning, sequence and social learning and numerosity. These results raise a fundamental question: how do insects generate such complexity with so few neurons? In this Research Topic, we aim at presenting novel findings and breakthrough approaches in the field of studies on insect cognition. Contributions should cover a broad spectrum of analyses, from behavioral quantifications of cognitive behavior in insects, to analyses of the neural circuits and molecular architectures responsible for cognition. Neural computation models accounting for cognitive processing based on minimal neural architectures will be also welcome. In this way, our Research Topic aims at expanding the information available on insect cognition focusing and at highlighting the mechanisms that underlie cognition in a miniature nervous system.